2018
DOI: 10.1080/14397595.2018.1452173
|View full text |Cite
|
Sign up to set email alerts
|

The impact of musculoskeletal diseases on the presence of locomotive syndrome

Abstract: Locomotive syndrome was associated with functional inconvenience in performing common daily activities involving the lower extremities and spine. Osteoporosis and aging were significantly associated with locomotive syndrome. The risk of locomotive syndrome may be decreased by treating comorbid osteoporosis and instituting exercise and diet-related modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The age-related increase was particularly remarkable among women, with the prevalence of LS stage 3 increasing from 2.9% in the age group 60-64 years to 18.4% in the age group > 75 years. Although it is known that female sex is one of the risk factors for LS [6], it could be confounded by the presence of osteoporosis [29]. In fact, this study indicated that the overall prevalence of osteoporosis in women was 21.9%, but was 1.4% in men; the proportion being the highest in LS stage 3.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The age-related increase was particularly remarkable among women, with the prevalence of LS stage 3 increasing from 2.9% in the age group 60-64 years to 18.4% in the age group > 75 years. Although it is known that female sex is one of the risk factors for LS [6], it could be confounded by the presence of osteoporosis [29]. In fact, this study indicated that the overall prevalence of osteoporosis in women was 21.9%, but was 1.4% in men; the proportion being the highest in LS stage 3.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the proportion of LBP in all the three LS stages was remarkably high (76.1 to 88.2%) as compared to that in the non-LS group. LBP has already been recognized as a risk factor for LS [29]. This attribution has not changed following the revision of the LS criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a relationship between exercise habits and LS among community-dwelling people. [28][29][30] Kota et al 31) reported that home exercise intervention led to improved physical function in communitydwelling elderly individuals. Maruya et al 32) showed the effectiveness of a 6-month exercise program for improving GLFS-25 scores.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our study showed that female gender increases the risk of LS up to 5 times. A positive history for chronic pain and chronic diseases increases the odds for LS, 4 and [15][16][17][18][19][20][21][22]. Regarding the high prevalence of LS in the elderly and its known correlation with these factors, screening the older people who are at risk for LS and taking proper precautions are highly recommended.…”
Section: Resultsmentioning
confidence: 99%